(untitled) (Web of Teachers: Inderscience Research, 2023)
This article mentions the relations and cooperation between the Central Asian countries and the Republic of Turkey in the field of culture and education. Also, the diplomatic relations of the republics, cultural events, opinions about higher educational institutions, cultural events between the five republics and Turkey, and innovations and cooperation in the field of education will be discussed.